L-Cysteine-capped CdTe quantum dots as a fluorescent probe for sequential detection of lysozyme and trypsin. (3rd May 2017) - Shi, Fanping; Liu, Siyu; Su, Xingguang
Abstract : A fluorescence assay for the sequential determination of lysozyme and trypsin was established based onl -cysteine capped CdTe quantum dots. Lysozyme with positive charges can interact withl -cysteine capped CdTe quantum dots. Lysozyme can be hydrolyzed into small fragments in the presence of trypsin, and the interaction betweenl -cysteine-capped CdTe QDs and lysozyme would be inhibited, which could be used for trypsin quantification. Abstract : In this work, we designed a simple and sensitive fluorescence probe for sequential detection of lysozyme and trypsin. Firstly, l -cysteine was chosen as a stabilizer to obtainl -cysteine-capped CdTe QDs. Lysozyme with positive charges can interact withl -cysteine capped CdTe quantum dots (QDs) via the special assembly between lysozyme andl -cysteine, resulting in the quenching of the fluorescence of CdTe QDs. Lysozyme can be hydrolyzed into small fragments in the presence of trypsin, and the interaction betweenl -cysteine-capped CdTe QDs and lysozyme would be inhibited, which could be used for trypsin quantification. There was a linear relationship between the fluorescence intensity of CdTe QDs and the lysozyme concentration in the range of 75–1000 ng mL −1 and another linear relationship between the fluorescence intensity of CdTe QDs and the logarithm of the trypsin concentration in the range of 10–500 ng mL −1 . The detection limits were 28.33 ng mL −1 for lysozyme and 8.35 ng mL −1 for trypsin, respectively. The established method showed a good selectivity for lysozyme and trypsin detection.